1999
DOI: 10.1016/s0029-7844(98)00476-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events reported by postmenopausal women in controlled trials with raloxifene

Abstract: Raloxifene had an adverse event profile distinct from HRT and unopposed estrogen and was well tolerated by postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(68 citation statements)
references
References 20 publications
1
65
1
1
Order By: Relevance
“…There was no difference between stroke and myocardial infarction between the two groups. Other large trials revealed similar results [13,16,22,26,28,29]. Consistent across these trials are the increases in hot flashes, night sweats, leg cramps and venous thromboembolic events (VTEs) with raloxifene compared to placebo.…”
Section: Safety Profilementioning
confidence: 66%
“…There was no difference between stroke and myocardial infarction between the two groups. Other large trials revealed similar results [13,16,22,26,28,29]. Consistent across these trials are the increases in hot flashes, night sweats, leg cramps and venous thromboembolic events (VTEs) with raloxifene compared to placebo.…”
Section: Safety Profilementioning
confidence: 66%
“…Because raloxifene is a SERM, it could theoretically block the effects of local Es on the vaginal mucosa. However, raloxifene was shown not to cause any adverse vaginal symptoms (4) in patients who do not have vaginal atrophy. Moreover, it has been demonstrated that women with evidence of preexisting vaginal atrophy who are treated with either low-dose conjugated E cream or nonhormonal moisturizer were not negatively influenced with concurrent raloxifene treatment for osteoporosis (5).…”
mentioning
confidence: 85%
“…In the Raloxifene Use for the Heart trial [72], raloxifene treatment demonstrated no difference in incidence of stroke but a 49% higher incidence of fatality due to stroke relative to placebo (59 vs 39 events, respectively; absolute risk increase of 0.7 per 1,000 woman-years). Raloxifene is also associated with an increased incidence of leg cramps and hot flushes [67,68,74].…”
Section: Raloxifenementioning
confidence: 99%